Educating for expected failure?: Ontological or soteriological perspectives on crossing the digital divide? - Conradie, Ernst M. (Stellenbosch theological journal, 2023)
This contribution takes as a point of departure an assessment of the impact of the digital divide with specific reference to the education sector in the South African context. A core problem is clearly that such a large proportion of learners drop out of secondary schools, while the pass rates at Bachelors level are also alarming. Does this imply that education takes place with a view to expected failure? This contribution explores the question what perspective Christianity and Christian theology can bring to this social reality. It suggests that this perspective is related to the perplexing question what education is there for in the first place. It surveys various options in this regard (knowledge, skills, virtues, values, worldviews) and then argues that education is also about developing interpretative and integrative frameworks, learning to see the world around us in a way that makes sense. On this basis various strategies to cross the deep divides in the South African education system are suggested. However, it is argued that "crossing" the digital divide should not be reduced to offering soteriological answers to questions regarding the nature of education that are primarily ontological in nature.